2019
DOI: 10.1016/j.ejrad.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in magnetic resonance findings between symptomatic and asymptomatic pre-collapse osteonecrosis of the femoral head

Abstract: The purpose of this study was to assess the differences in magnetic resonance (MR) findings between the symptomatic and asymptomatic pre-collapse stage of osteonecrosis of the femoral head (ONFH). Materials and methods: This study reviewed 123 consecutive hips in 91 patients in the pre-collapse stage of ONFH based on plain radiographic findings. These 123 hips were divided into symptomatic and asymptomatic groups according to the pain domain score in the Harris hip score system. Bone marrow edema (BME), synovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…In addition, bone marrow edema induced by subclinical femoral head collapse may reduce radiodensity on plain radiographs because it causes changes in trabecular hydration. 25,26 Hatanaka et al 26 In this study, the mean HU value of the lateral boundary in ONFH patients with subsequent femoral head collapse was higher than those in patients without subsequent collapse, while the mean HU value of the anterosuperior portion of the femoral head demonstrated no significant difference between the two groups. One proposed hypothesis is that the mechanism of collapse in ONFH involves the effects of the focal concentration of shear stress at the boundary of the thickened sclerotic boundary and necrotic bone.…”
Section: Differences In Hu Values Of the Lateral Boundary Between Omentioning
confidence: 47%
See 1 more Smart Citation
“…In addition, bone marrow edema induced by subclinical femoral head collapse may reduce radiodensity on plain radiographs because it causes changes in trabecular hydration. 25,26 Hatanaka et al 26 In this study, the mean HU value of the lateral boundary in ONFH patients with subsequent femoral head collapse was higher than those in patients without subsequent collapse, while the mean HU value of the anterosuperior portion of the femoral head demonstrated no significant difference between the two groups. One proposed hypothesis is that the mechanism of collapse in ONFH involves the effects of the focal concentration of shear stress at the boundary of the thickened sclerotic boundary and necrotic bone.…”
Section: Differences In Hu Values Of the Lateral Boundary Between Omentioning
confidence: 47%
“…A previous report demonstrated that the number of osteoclasts significantly increased only after the occurrence of femoral head collapse in patients with ONFH, 24 which may result in increased radiolucency due to bone resorption around the necrotic lesion. In addition, bone marrow edema induced by subclinical femoral head collapse may reduce radiodensity on plain radiographs because it causes changes in trabecular hydration 25,26 . Hatanaka et al 26 demonstrated bone marrow edema on MRI, indicating a subclinical subchondral fracture, even when no apparent collapse was found on plain radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Legg-Calve-Perthes disease is also a common etiology of childhood osteonecrosis, usually with extensive and severe involvement of the epiphysis [32,33]. Symptoms, as one of the recognized prognostic factors of disease progression in most types of AVN, showed a significant relationship with the ARCO stage in this study [26,34,35]. According to our data, hip symptoms, such as hip pain, limp, and restricted hip function, were recorded in 68 of 115 cases, 85.3% of which had progressed to femoral head collapse.…”
Section: Retrospective Studysupporting
confidence: 52%
“…The former is a widely recognized adverse effect of femoral head remodelling, and the latter increasingly exacerbates hip degeneration. Other recognized prognostic factors of progression of femoral head collapse for most types of osteonecrosis of femoral head, such as the initial degree of femoral head collapse [27], JIC classification [15] and symptoms [28], show no apparent relation to severe hip deformity and degeneration. Therefore, these factors did have value for predicting femoral head collapse, but after collapse, not all hip showed further progression to severe hip deformity and degeneration.…”
Section: Femur Head Necrosis In the Paediatric Population Can Be Indumentioning
confidence: 99%